1981
DOI: 10.1007/bf00443011
|View full text |Cite
|
Sign up to set email alerts
|

Fungal contamination and mycotoxin-producing potential of dried beans

Abstract: A total of 604 samples of about 7 different types of beans was examined to determine their mycological profiles, and suitability for use as solid substrates for mycotoxin production. All of the samples were collected from bean jam makers in Tokyo by the official food examiners. Genera Penicillium and Aspergillus were predominant, and genus Wallemia was also found commonly in all types of beans. Mycotoxin-producing Aspergillus strains were isolated from 52 samples of beans, approximately 9% of the total. The hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
6

Year Published

1983
1983
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 16 publications
4
28
0
6
Order By: Relevance
“…Hitokoto et al (1978) demonstraram que fungos dos gêneros Penicillium, Aspergillus, Rhizopus, Mucor, Cladosporium e Aureobasidium spp. encontram-se freqüentemente associados à drogas vegetais; no entanto, fungos produtores de micotoxinas somente foram encontrados em um nível de 2%.…”
Section: Pesquisa De Patógenos Específicosunclassified
“…Hitokoto et al (1978) demonstraram que fungos dos gêneros Penicillium, Aspergillus, Rhizopus, Mucor, Cladosporium e Aureobasidium spp. encontram-se freqüentemente associados à drogas vegetais; no entanto, fungos produtores de micotoxinas somente foram encontrados em um nível de 2%.…”
Section: Pesquisa De Patógenos Específicosunclassified
“…They found no contamination with aflatoxins (Romagnoli, Menna, Gruppioni, & Bergamini, 2007). In a study by Hitokoto et al, aflatoxins were not detected in the 49 powdered herbal drugs (Hitokoto, Morozumi, Wauke, Sakai, & Kurata, 1978). Ten percent of the tablets of Cascara sagrada dried bark were contaminated with aflatoxins in Argentina (Trucksess & Scott, 2008).…”
Section: Herbs and Spicesmentioning
confidence: 95%
“…The presence of fungal species in crude herbal drugs and their role in spoilage of crude drug was reported by Matsushima et al (1957). Hitoshi et al (1978) reported three different kinds of mycotoxins i.e. aflatoxin, sterigmatoceistin and orchratoxin produced by different fungal genera from 14 powdered herbal drug samples.…”
Section: Microbial Contamination Of Herbal Drugsmentioning
confidence: 99%
“…Fungal count enumeration and mycotoxin production were carried out by some workers. Important contributions are that of Hitoshi et al, 1978;Nagi Halim Azij et al, 1998;Roy and Chaurasia, 1998. Fragmentary reports on microbial contaminants of raw and powdered herbal drugs provide the picture of herbal drugs quality as well as their possible effect on health management.…”
Section: Status Of Microbial Contaminants Of Herbal Drugsmentioning
confidence: 99%
See 1 more Smart Citation